Effect of quinoa flour on fermentation, physicochemical and sensory properties of goat milk yogurt - Ajbli, Nouhaila; Zine-eddine, Yassine; Laaraj, Salah; Ait El Alia, Omar; Elfazazi, Kaoutar; Bouhrim, Mohamed; Herqash, Rashed N.; Shahat, Abdelaaty A.; Benbati, Mohamed; Kzaiber, Fouzia; Boutoial, Khalid (Frontiers in Sustainable Food Systems, 2025)
IntroductionGoat milk (GM) is highly valued for its rich nutritional content, easy digestibilityand low allergenic potential, making it an excellent alternative in the dairy industry.Quinoa, an Andean pseudo cereal, offers significant nutritional benefits, including high protein, fiber, and antioxidant properties. This study aims to assess the impact of adding quinoa flour (QF) on the fermentation, physicochemical and sensory properties of goat milk yogurt (GMY), addressing a research gap regarding the use of roasted quinoa flour (RoQF) in GMY production.MethodologieWhite and red quinoa flours, both roasted and unroasted, were incorporated at 0.5, 1, and 1.5% in the yogurt. The analysis focused on fermentation time, lactic acid production, pH, macronutrient composition, product stability, and sensory evaluation.Results and discussionThe inclusion of 1% quinoa flour (QF) significantly increased the yogurt’s macronutrient content (p ≤ 0.05) compared to the control test, where protein content was 4.01 and fat content was 3.94 (g/100 g). Protein content increased by 0.1 to 0.17 (g/100 g), reaching 4.18; 4.15; 4.15 and 4.11 (g/100 g) for goat milk yogurt with white quinoa flour (GMYWQF), goat milk yogurt with red quinoa flour (GMYRQF), goat milk yogurt with roasted white quinoa flour (GMYRoWQF) and goat milk yogurt with roasted red quinoa flour (GMYRoRQF), respectively. Similarly, fat content increased by 0.03 to 0.09 (g/100 g) reaching 3.98, 4.03, 3.97, and 3.98 (g/100 g) for GMYWQF, GMYRQF, GMYRoWQF, and GMYRoRQF, respectively. These changes led to reduced fermentation time, minimizing it to 4 h, by promoting faster lactic acid production and lowering the pH more efficiently compared to the control test, indicating more efficient fermentation. Sensory analysis revealed that QF significantly improved the texture and flavor of the yogurt (p ≤ 0.05), with roasted quinoa flour (RoQF) further significantly enhancing consumer acceptability (p ≤ 0.05), by reducing the strong flavor of GM. Additionally, QF significantly improved yogurt stability, enhancing texture and shelf life (p ≤ 0.05). These findings emphasize the value of QF as an ingredient in GMY: significantly (p ≤ 0.05) increasing the protein content and improving texture, resulting in a more stable product with reduced Syneresis; Roasting the QF further significantly (p ≤ 0.05) enhances its sensory qualities, effectively decreasing the goat flavor, which is often less favored by some consumers, thus increasing overall acceptability. These advantages have important implications for refining dairy product formulations.